Expression Patterns of Macrophage Migration Inhibitory Factor and Its Gene Variants (MIF-173 G˃C) in Verruca Vulgaris - Hassan MH; Abuhamdah S; Elsadek BE; Abdelwahab A; Abd-Elhamid TH; Fayed HM; Abbass A; Abdallah AAM; Mohamed M; Abd-Elmagid WM (Dove Medical Press, 2022)
Mohammed H Hassan,1 Sawsan Abuhamdah,2,3 Bakheet EM Elsadek,4 Ashraf Abdelwahab,5 Tarek Hamdy Abd-Elhamid,6 Hanan M Fayed,7 Amany Abbass,8 Ahmed Alamir Mahmoud Abdallah,9 Marwa Mohamed,5 Wafaa Mohamed Abd-Elmagid5 1Department of Medical Biochemistry, Faculty of Medicine, South Valley University, Qena, 83523, Egypt; 2College of Pharmacy, Al Ain University, Abu Dhabi, United Arab Emirates; 3Department of Biopharmaceutics and Clinical Pharmacy, Faculty of Pharmacy, The University of Jordan, Amman, Jordan; 4Department of Biochemistry and Molecular Biology, Faculty of Pharmacy, Al-Azhar University, Assiut Branch, Assiut, 71524, Egypt; 5Department of Dermatology, Venereology and Andrology, Faculty of Medicine, Sohag University, Sohag, Egypt; 6Department of Histology and Cell Biology, Faculty of Medicine, Assiut University, Assiut, Egypt; 7Department of Chemical and Clinical Pathology, Faculty of Medicine, South Valley University, Qena, 83523, Egypt; 8Department of Chemical and Clinical Pathology, Faculty of Medicine, Sohag University, Sohag, Egypt; 9Medical Biochemistry Department, Faculty of Medicine, Sohag University, Sohag, EgyptCorrespondence: Mohammed H Hassan, Department of Medical Biochemistry, Faculty of Medicine, South Valley University, Qena, 83523, Egypt, Tel +20 109 8473605, Email Mohammedhosnyhassaan@yahoo.com; mohammedhosnyhassaan@med.svu.edu.egIntroduction: Verruca vulgaris is a benign hyperkeratotic proliferation of the epidermis. Few studies look at the differences in serum and tissue macrophage migration inhibitory factor (MIF) levels in verruca vulgaris, as well as its gene polymorphisms that have yet to be explored. The current study provided in-depth evaluation of MIF in serum and tissues of patients with verruca vulgaris, and establishes for the first time the possible association of MIF gene polymorphisms with common warts.Methods: This case-control study included 50 patients who were diagnosed clinically as common warts in comparison with 50 age and sex-matched controls. Clinical examination was done on all included cases. Serum MIF was measured using enzyme-linked immunosorbent assay (ELISA), while its tissue expression was analyzed using Western blotting and immunohistochemical techniques for the included participants. Analysis of MIF-173 G˃C single nucleotide polymorphism was performed by polymerase chain reaction (PCR) using restriction fragment length polymorphism (RFLP) technique.Results: The overall results revealed significantly lower MIF tissue expression in lesional and perilesional skin biopsies from cases compared to the controls using Western blot and immunohistochemical analysis. Yet, the difference in the serum MIF levels between cases and controls was not significant (p ˃ 0.05). GC genotype of the studied MIF rs755622 G>C SNP could be considered as a protective genetic factor against the occurrence of verruca vulgaris among Egyptians with OR (95% CI) equal 0.444 (0.199- 0.989).Conclusion: MIF and its genetic variants are thought to play a pathogenic role in verruca vulgaris development and recurrence.Keywords: macrophage migration inhibitory factor, MIF rs755622 G>C SNP, common warts, RFLP-PCR, western blot, immunohistochemistry